From dental caries prevention to remineralization: the impact of sodium fluoride (NaF) and titanium tetrafluoride (TiF4) varnishes on white spot lesions and the modulation of the oral microbiome in a high-caries-risk population - Moraes, Samanta Mascarenhas (2024)
This study investigated the effectiveness of fluoride varnishes in preventing and remineralizing white spot lesions (WSLs) and their impact on the oral microbiome in orthodontic patients. To compare the effectiveness of titanium tetrafluoride (TiF4) with sodium fluoride (NaF) varnish in preventing and remineralizing effects on WSLs a randomized, placebo-controlled, double-blinded trial was conducted. Sixty-five adolescents, with at least one active non-cavitated (ANC) caries lesion, were divided into three groups: placebo varnish (G1), NaF varnish (G2), and TiF4 varnish (G3). Varnish applications were administered weekly for the first 4 weeks, followed by evaluations at 6 and 12 months. Outcomes measured included prevention of new WSLs and reversal/progression of existing WSLs using Nyvad and ICDAS indices and quantitative light-induced fluorescence (QLF). Statistical analyses, including Chi-square, ANOVA, and Kruskal-Wallis tests were performed. Bonferroni test was used as a post hoc for multiple comparisons and the significance level was set at 0.05. At baseline, no significant differences were observed among the groups. However, after 12 months, the TiF4 varnish group showed the highest efficacy in reducing WSL prevalence and progression, with a notable decrease in incidence compared to the other groups. Specifically, the incidence of WSLs at 12 months was 10.2% (G1), 5.6% (G2), and 1.4% (G3). In terms of regression, 14% of teeth initially scored as Nyvad 1 in the TiF4 group regressed to Nyvad 0, compared to 6.8% and 1% in the NaF and placebo groups, respectively. Progression was minimal in the TiF4 group (0.9%) compared to the NaF (7.7%) and placebo (14.9%) groups. QLF analysis also supported these findings, with TiF4 showing the most significant reduction in integrated fluorescence loss, indicating effective remineralization. Additionally, the study explored the impact of these varnishes on the oral microbiome using 16S rRNA sequencing in a subset of 13 participants from the ongoing clinical trial. These participants underwent a four-stage randomized crossover study involving non-treatment, professional prophylaxis (PP), PP + NaF varnish, and PP + TiF4 varnish. Supragingival biofilm samples were collected for microbiome analysis. The Shannon Diversity index revealed significant differences between the varnish treatments and the non-treatment group, with no significant differences between NaF and TiF4 varnishes. The most abundant genera were: Veillonella (7.6%, 10.6%, 9.4%, 5.7%), Corynebacterium (8.2%, 7.3%, 6.8%, 10.4%), Neisseria (4.0%, 9.2%, 9.6%, 9.6%), and Streptococcus (5.2%, 8.0%, 7.4%, 10.1%), respectively in groups non-treatment, PP, PP + NaF varnish, and PP + TiF4 varnish. Both NaF and TiF4 varnishes effectively modified the biofilm microbiota, suggesting their impact on managing caries risk in a high-caries-risk population. Overall, while both fluoride varnishes were effective in preventing and remineralizing WSLs, TiF4 varnish demonstrated superior control over WSLs during orthodontic treatment. Additionally, both varnishes influenced the oral microbiome, contributing to shifts that could play a role in caries prevention and management. These results highlight the potential of TiF4 varnish as a more effective preventive strategy in orthodontic patients at high risk for caries, with significant implications for both clinical practice and future research in dental caries prevention and biofilm management.